Comparative Analysis of Data Mining With Big Data Using WEKA Software Tool - Rao Putta, Srinivasa (International Journal of Computer Sciences and Engineering, 2019)
Big data has become more popular as people and organizations realize the importance and the value that the data has in formulating important information. As the data continue to increase, some challenges arise on the methods or techniques that are needed to be used in extracting meaningful information from the big data. Increase in data has led the researchers to make expansions on the existing data mining techniques to help with adapting to the evolving nature of big data thus leading to the development of new analytical techniques. Research has led to the development of various data mining techniques used on big data. It is, therefore, necessary to evaluate and compare different data mining techniques for big data.